2020
DOI: 10.1007/s13762-020-02640-0
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol mass and major composition characterization of ambient air in Ho Chi Minh City, Vietnam

Abstract: In this study, we compared particulate matter (PM) measurements (including PM 10 , PM 2.5 , heavy metals, and black carbon) between the 2014 rainy season (August-October) and dry season (March-May) in different urban areas within Ho Chi Minh City, Vietnam. PM 10 and PM 2.5 concentrations varied widely among the sampling sites during each season, with relative PM concentrations increasing in the following order: city zoo < rural area < residential area < roadside < city road. Higher PM 10 and PM 2.5 concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Table summarizes the comparison of trace metal concentration from current monitoring sites to those in other cities from different parts of the world. ,, Several of the metals (V and Se) in PM 2.5 in this study were higher than those observed in other cities including Bangi around Kuala Lumpur in Malaysia. The concentration of PM 2.5 -bound V, Cu, Zn, As, and Se at the present study sites was higher than that in neighboring Bangkok and Singapore.…”
Section: Resultsmentioning
confidence: 58%
“…Table summarizes the comparison of trace metal concentration from current monitoring sites to those in other cities from different parts of the world. ,, Several of the metals (V and Se) in PM 2.5 in this study were higher than those observed in other cities including Bangi around Kuala Lumpur in Malaysia. The concentration of PM 2.5 -bound V, Cu, Zn, As, and Se at the present study sites was higher than that in neighboring Bangkok and Singapore.…”
Section: Resultsmentioning
confidence: 58%
“…Heavy metals are transported into the environment, especially water sources and easily absorbed by living organisms. Due to their pronounced toxicity, these heavy metals are important for monitoring the environment (water, wastewater, air, solid waste, and organisms) [ 95 , 97 , 98 ]. Monitoring water contamination is essential for environmental conservation and the prevention of illnesses.…”
Section: Application Of Biosensor To Environmental Monitoringmentioning
confidence: 99%
“…[32][33][34][35]. IPs are ususaly accompanied by some environmental disadvantages, including more carbon emissions and ecological stress/pressures [36,37]. Recently, a case study of typical LCIPs was conducted to examine the economic and ecological benefits [38].…”
Section: Case Study Of Trang Bang Ipmentioning
confidence: 99%